Colonial scripts: how Western political discourse facilitates the erasure of Palestinian humanity - Ibrahim Fraihat (20280354) (2025)
The events of 7 October and the ensuing Israeli bombardment of Gaza have emerged as a critical juncture in global politics. This war did not unfold in isolation; rather, the positions taken by various international actors significantly shaped its trajectory. In particular, the early and sustained support of certain superpower governments played a decisive role in enabling the continuation of hostilities and facilitating the commission of Israeli atrocities. This paper examines how Western political leaders – including US President Joe Biden, UK Prime Minister Rishi Sunak, French President Emmanuel Macron, and German Chancellor Olaf Scholz – rhetorically enabled this devastation. Through statements that dehumanised Palestinians and framed the conflict in reductive and ahistorical terms, these leaders contributed to a discourse that normalised disproportionate violence and erased Palestinian personhood. The study identifies five rhetorical strategies that facilitated this erasure: the reductive ‘Israel–Hamas’ framing of the conflict, the dehistoricisation of Palestinian suffering, the denial of Palestinian self-defence, the objectification of Palestinian children, and the selective empathy in addressing the hostage crisis. Other Information Published in: Third World Quarterly License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/01436597.2025.2549774